Analisis Yuridis Terhadap Hak-Hak Atas Tanah Yang Berada Di Atas Hak Pengelolaan Pelabuhan - Lovelly Dwina Dahen (Jurnal Ilmu Hukum, 2012)
The role of sea ports in the future will be increasinglyimportant, it is necessary to improve the quality ofservice (quality of services). According to the rules ofthe Decree of Directors. (Limited) II No PortsIndonesia. HK.56/1/2/PI.II-2000 dated January 3,2000 submission of the use of portions of land can beprovided with a port HPL Broking and Right to Leasethe building. This is contrary to the Regulation of theMinister of Interior No.1 of 1977, in which rights canbe given to land management rights are Broking andRight to Use.